2020
DOI: 10.3390/geosciences10090374
|View full text |Cite
|
Sign up to set email alerts
|

Storm-Induced Boulder Displacements: Inferences from Field Surveys and Hydrodynamic Equations

Abstract: The storm of 12–13 November 2019 provoked the displacements of boulders on a central Mediterranean rocky coast; with reference to a selected area, prone to boulder production and geomorphologically monitored for years, a field-oriented study approach was applied for the phenomenon, by collating data concerning the pre-storm locations and kinematics of these boulders. The number of displaced boulders is 11, that is in terms of the morphological imprint of a specific storm, one of the major study cases for the M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…589 by [10]. Here we observe how even displaced coarse boulders may not be recognized 590 by the multi-temporal satellite imagery (Figure A2).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…589 by [10]. Here we observe how even displaced coarse boulders may not be recognized 590 by the multi-temporal satellite imagery (Figure A2).…”
mentioning
confidence: 82%
“…398 we know that also numerous smaller clasts have changed position due to the November 399 12-13 storm [10].…”
mentioning
confidence: 99%
“…Location Meteorological Event(s) Mastronuzzi and Sansò (2004) [16] South Adriatic identified Barbano et al (2010) [47] West Ionian identified Barbano et al (2011) [48] West Ionian roughly identified Hoffmeister et al ( 2013) [49] East Ionian roughly identified Shah-Hosseini et al ( 2013) [50] Gulf of Lion not identified Torab and Dalal (2015) [51] Eastern Mediterranean not identified Biolchi et al ( 2016) [52] South Central Mediterranean not identified Causon Deguara and Gauci (2017) [53] South Central Mediterranean not identified Piscitelli et al ( 2017) [54] Gulf of Lion not identified Roig-Munar et al ( 2017) [55] Balearic Sea identified Galea et al ( 2018) [46] South Central Mediterranean identified Pepe et al ( 2018) [56] South Tyrrhenian not identified Roig-Munar et al ( 2018) [57] Balearic Sea not identified Biolchi et al (2019a) [17] North Adriatic identified Biolchi et al (2019b) [58] North Adriatic identified Delle Rose et al (2020) [59] North Ionian identified Hoffmeister et al (2020) [60] East Ionian not identified Mottershead et al (2020) [61] South Central Mediterranean not identified Scicchitano et al (2020) [62] West Ionian identified Delle Rose et al ( 2021) [45] North Ionian identified…”
Section: Author(s) and Yearmentioning
confidence: 99%
“…Some articles address two or more stretches of Mediterranean coasts [45,48,51,52,56,57,60], thus the screening process has allowed the identification of 44 sites showing evidence or clues of CBD production/activation as a result of recent (i.e., during about the last halfcentury) storms. Many articles concern cases belonging to the central Mediterranean [16,17,[45][46][47][48][49]52,53,56,[58][59][60][61][62], (see Figure 3). Some studies are relative to the western Mediterranean [50,54,55,57], while only one study to the eastern Mediterranean [51].…”
Section: Author(s) and Yearmentioning
confidence: 99%
“…MFV is arguably a more suitable metric than minimum wave height (MWH). Although MWH calculations have also proven popular (Deguara & Gauci, 2017;Delle Rose et al, 2020;Huang et al, 2020;Mottershead et al, 2014;Roig-Munar et al, 2019), the validity of this metric is coming under increasing criticism because direct relationships cannot easily be established between clast dimensions and wave heights (Cox et al, 2020;Kennedy et al, 2019).…”
Section: Hew Magnitudementioning
confidence: 99%